Methane Production and Methanogenic Archaea in the Digestive Tracts of Millipedes (Diplopoda) - Šustr, Vladimír (Public Library of Science, 2014)
Methane production by intestinal methanogenic Archaea and their community structure were compared among phylogenetic lineages of millipedes. Tropical and temperate millipedes of 35 species and 17 families were investigated. Species that emitted methane were mostly in the juliform orders Julida, Spirobolida, and Spirostreptida. The irregular phylogenetic distribution of methane production correlated with the presence of the methanogen-specific mcrA gene. The study brings the first detailed survey of methanogens’ diversity in the digestive tract of millipedes. Sequences related to Methanosarcinales, Methanobacteriales, Methanomicrobiales and some unclassified Archaea were detected using molecular profiling (DGGE). The differences in substrate preferences of the main lineages of methanogenic Archaea found in different millipede orders indicate that the composition of methanogen communities may reflect the differences in available substrates for methanogenesis or the presence of symbiotic protozoa in the digestive tract. We conclude that differences in methane production in the millipede gut reflect differences in the activity and proliferation of intestinal methanogens rather than an absolute inability of some millipede taxa to host methanogens. This inference was supported by the general presence of methanogenic activity in millipede faecal pellets and the presence of the 16S rRNA gene of methanogens in all tested taxa in the two main groups of millipedes, the Helminthophora and the Pentazonia.